A questionnaire study on university students' awareness of forensic chemistry - Raghda Makia; Khalid Zainulabdeen; Akram Al-Sabbagh; Alaa A. Rashad; Waled Abdo Ahmed; Eamd Yousif (Indonesian Journal of Chemical Education, 2024)
This article delves into the growing significance of forensic science within criminal investigations and court proceedings, focusing on the pivotal role of forensic chemistry. Forensic chemistry, a sub-discipline of forensic science, is critical in examining physical evidence, encompassing substances like drugs, explosives, and toxic compounds. However, despite the escalating demand for forensic chemists in the job market, the public's awareness and knowledge of forensic chemistry, including university students, remains inadequately explored. Through a questionnaire study, this article presents the results that elucidate the extent of awareness and knowledge regarding forensic chemistry among university students. Additionally, this research examines the attitudes and perceptions of university students towards forensic chemistry education and career opportunities. The implications derived from the findings of this study are profound and have far-reaching consequences, specifically concerning forensic chemistry education, career development, and the enhancement of public comprehension surrounding forensic science.